Manejo de postcosecha del cultivo de papaya (Carica papaya L.) y su impacto en la economía del productor ecuatoriano - Quinatoa Añamañay, Verónica Abigail (2022)
The development of the document dealt with the postharvest management of the papaya (Carica papaya L.) crop and its impact on the producer's economy. The cultivation of papaya is an important product for small farmers, especially in rural areas, where they are dedicated to its planting and production and often have ignorance or lack of infrastructure and economic resources to carry out post-harvest processes for later commercialization. The conclusions with a good adequate management in the post-harvest of the papaya crop, which are carried out, there would be no losses during the harvest and its comercialización. Postharvest losses must be reduced, considering that the fruit, even after harvesting, maintains its respiration, maturing and initiating senescence processes; It is also constantly exposed to loss of water and fresh weight due to perspiration and other physiological phenomena. Reception, washing and quality control are carried out at the packing plant. The producer is affected by producing fruits that are not suitable for marketing because, at the time of harvest, he is affected by poor handling of the harvest by field workers, this causes the fruit to deteriorate progressively and affects the quality of the fruit and therefore its commercialization that definitely causes an impact on the economy of the producer.